Flavonoid intake and the risk of age-related cataract in China's Heilongjiang Province - Ma, Yingna (Food Nutr Res, 2015)
BACKGROUND/OBJECTIVES: Epidemiological evidence suggests that diets rich in flavonoids may reduce the risk of developing age-related cataract (ARC). Flavonoids are widely distributed in foods of plant origin, and the objective of this study was to evaluate retrospectively the association between the intakes of the five flavonoid subclasses and the risk of ARC. SUBJECTS/METHODS: A population-based case-control study (249 cases and 66 controls) was carried out in Heilongjiang province, which is located in the northeast of China, and where intakes and availability of fresh vegetables and fruits can be limited. Dietary data gathered by food-frequency questionnaire (FFQ) were used to calculate flavonoid intake. Adjusted odds ratio (OR) and 95% confidence interval (CI) were estimated by logistic regression. RESULTS: No linear associations between risk of developing ARC and intakes of total dietary flavonoids, anthocyanidins, flavon-3-ol, flavanone, total flavones or total flavonols were found, but quercetin and isorhamnetin intake was inversely associated with ARC risk (OR 11.78, 95% CI: 1.62–85.84, p<0.05, and OR 6.99, 95% CI: 1.12–43.44, p<0.05, quartile 4 vs. quartile 1, respectively). CONCLUSION: As quercetin is contained in many plant foods and isorhamnetin in very few foods, we concluded that higher quercetin intake may be an important dietary factor in the reduction of the risk of ARC.